Decay out of a superdeformed band - Gu, Jian-zhong; Weidenmüller, Hans-Arwed (Nuclear physics. A, Nuclear and hadronic physics, 2000)
Using a statistical model for the normally deformed states and for their coupling to a member of the superdeformed band, we calculate the ensemble average and the fluctuations of the intensity for decay out of the superdeformed band and of the intraband decay intensity. We show that both intensities depend on two dimensionless variables: the ratio Γ↓/ΓS and the ratio ΓN/d. Here, Γ↓ is the spreading width for the mixing of the superdeformed and the normally deformed states, d is the mean level spacing of the latter, and ΓS(ΓN) is the width for gamma decay of the superdeformed state (of the normally deformed states, respectively). This parametric dependence differs from the one predicted by the approach of Vigezzi et al., where the relevant dimensionless variables are ΓN/ΓS and Γ↓/d. We give analytical and numerical results for the decay intensities as functions of the dimensionless variables, including an estimate of the error incurred by performing the ensemble average, and we present fit formulas useful for the analysis of experimental data. We compare our results with the approach of Vigezzi et al., and establish the conditions under which this approach constitutes a valid approximation.
Available online 2 February 2000
Gesehen am 01.12.2020